2015
DOI: 10.1186/s12879-015-1047-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unreported tuberculosis cases in Spanish hospitals

Abstract: BackgroundUnder-reporting of tuberculosis (TB) cases complicates disease control, hinders contact tracing and alters the accuracy of epidemiological data, including disease burden. The objective of the present study is to evaluate the proportion of unreported TB cases in Spanish healthcare facilities and to identify the associated factors.MethodsA multi-center retrospective study design was employed. The study included TB cases diagnosed in 16 facilities during 2011–2012. These cases were compared to those rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
6
9
0
1
Order By: Relevance
“…This may be related to a higher rate of comorbidity in patients aged 65 or older, which could necessitate treatment in non-TB-designated health facilities. This is consistent with the bivariate analysis in a study conducted in Spain [14]. We also found that the [39].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This may be related to a higher rate of comorbidity in patients aged 65 or older, which could necessitate treatment in non-TB-designated health facilities. This is consistent with the bivariate analysis in a study conducted in Spain [14]. We also found that the [39].…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings are similar to some studies conducted in other countries in which the under-reporting rate of TB ranged from 6-68% [14,16,17,[24][25][26][27][28][29][30]. Fatima et al estimated that almost 68% of persons with TB were not noti ed to the NTP in Pakistan, many because a large private sector did not report to the NTP [28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, no revision of TB under-reporting was included in this study, but TB underreporting was low, 11.1% (3/24), in the Hospital General of Castellon during 2011-2012 period. 38 From PTB-associated factors, health promotion and preventive and control measures could be addressed. Several actions may be proposed, including the battle against poverty and housing shortage; promotion of full employment; health education against the consumption of tobacco, alcohol, and other drugs; and finally accurate control of TB patient and their contacts.…”
Section: Discussionmentioning
confidence: 99%